The Impact of Industrial Sociology on Vocational Education and Skill Development in Nigeria: Bridging the Gap between Education and Labor Market Needs - Odey, Stephen Adi (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2025)
Industrial sociology, as a field of study, examines the interplay between social structures, work organizations, and labor markets. In Nigeria, the disconnect between vocational education and the labor market has resulted in high unemployment rates, underemployment, and a skills mismatch. This paper explores the role of industrial sociology in addressing these challenges by analyzing how sociological insights can inform vocational education and skill development programs. By examining the social dynamics of work, organizational behavior, and labor market demands, this paper argues for a more integrated approach to vocational education that aligns with the needs of Nigeria’s evolving economy. The study concludes with policy recommendations for bridging the gap between education and labor market needs, emphasizing the importance of collaboration between educational institutions, industries, and policymakers.